Integrating Smart Assistants into Kazakh Language Learning: Impacts on Learner Engagement (Eurasian Journal of Philology Science and Education, 2026)
The rapid advancement of digital technologies has significantly transformed contemporary educational practice, contributing to the emergence of smart education as a learner-centred and technology-enhanced model of instruction. This article examines the effectiveness of smart assistants in language learning, with particular emphasis on the development of listening, speaking, and pronunciation skills. The study employed a quasi-experimental mixed-methods design and involved undergraduate students divided into experimental and control groups. The experimental group completed language-learning activities supported by smart assistants (including guided speaking practice and pronunciation training), whereas the control group followed traditional instructional methods.Quantitative data were collected through pre- and post-tests, while qualitative data were obtained via questionnaires and semi-structured interviews. This design made it possible to compare not only measurable learning outcomes but also students’ attitudes, motivation, and affective factors associated with oral communication. The results indicated that students who used smart assistants demonstrated stronger gains in communicative skills than those taught traditionally. In addition, the use of smart assistants was associated with increased learning motivation, reduced speaking anxiety, and greater confidence in oral interaction. The study concludes that smart assistants can function as an effective supplementary tool in blended-learning contexts by supporting personalisation, flexibility, and accessibility. Although limitations remain, particularly in speech-recognition accuracy and the depth of context-sensitive feedback, these technologies offer substantial pedagogical potential and expand opportunities for modern language education.Keywords: smart education, smart assistants, language learning, digital technologies, speaking skills, blended learning.